PEMBERDAYAAN KELUARGA MENGHADAPI PANDEMI COVID-19 MELALUI PROGRAM PENDAMPINGAN USAHA JILBAB KAIN PERCA MENDONGKRAK PEREKONOMIAN WARGA UJUNG PANGKAH-GRESIK DI ERA PANDEMI COVID 19 - Sulistiyani (Universitas PGRI Adi Buana Surabaya, 2022)
Today the world is facing a post-disaster, namely the Covid-19 pandemic, so the government has limited all activities outside the home. One of the government's steps to maintain economic conditions is to strengthen the role of MSMEs and maintain health. The purpose of this service activity is according to the objectives of MSMEs, which include: the hijab trend is growing from time to time, especially in the field of women's fashion. Departing from this phenomenon, the service team hopes that the women in Ujung Pangkah-Gresik can create hijab creations with patchwork so that they themselves can create their own without spending a lot of capital. Therefore, this service team intends to teach the skills of making hijabs that vary from patchwork to women so that they can create and market their own hijab creations or develop it as a home industry in this era of the covid 19 pandemic. The method used in this activity is. The first is the introduction and socialization of the hijab from patchwork. The introduction in question is to provide examples of products and how to make them. Second, scheduling is training with systematic and unidirectional time management. Availability and cooperation with Partners. The result of this service, various forms of hijab from patchwork that can be circulated in the market whose patterns and prices vary greatly. With a piece of patchwork and added with a few beads, the two materials can be transformed into an elegant hijab with a market price of tens of thousands .